2009
DOI: 10.1165/rcmb.2008-0338oc
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Stimulates Na+/K+/2Cl Cotransport via PTK-Dependent Mechanisms in Human Airway Epithelium

Abstract: We investigated regulatory mechanisms of Cl(-) secretion playing an essential role in the maintenance of surface fluid in human airway epithelial Calu-3 cells. The present study reports that quercetin (a flavonoid) stimulated bumetanide-sensitive Cl(-) secretion with reduction of apical Cl(-) conductance, suggesting that quercetin stimulates Cl(-) secretion by activating an entry step of Cl(-) across the basolateral membrane through Na(+)/K(+)/2Cl(-) cotransporter (NKCC1). To clarify the mechanism stimulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 43 publications
3
30
1
Order By: Relevance
“…Although capsaicin inhibited I SC due to suppression of basolateral channels and transporters, it conversely caused a sustained increase in apical I Cl , reflecting the conductance of CFTR, a cAMP-activated Cl 2 channel (20), indicating that anion uptake across the basolateral membrane is the ratelimiting step that determines the overall secretion capacity (16,22,24,29). In addition, the result that the basolateral Cl 2 conductance increased by forskolin was inhibited by capsaicin excludes the possibility that apical Cl 2 transport would be reduced by intracellular Cl 2 loss as a result of basolateral Cl 2 release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although capsaicin inhibited I SC due to suppression of basolateral channels and transporters, it conversely caused a sustained increase in apical I Cl , reflecting the conductance of CFTR, a cAMP-activated Cl 2 channel (20), indicating that anion uptake across the basolateral membrane is the ratelimiting step that determines the overall secretion capacity (16,22,24,29). In addition, the result that the basolateral Cl 2 conductance increased by forskolin was inhibited by capsaicin excludes the possibility that apical Cl 2 transport would be reduced by intracellular Cl 2 loss as a result of basolateral Cl 2 release.…”
Section: Discussionmentioning
confidence: 99%
“…In the regulation of basolateral anion transporters, involvement of basolateral membrane Cl 2 and K 1 conductance must be considered (21,24). In the permeabilized monolayer pretreated with apical nystatin (50 mM) under the basolateral-to-apical Cl 2 concentration gradient, forskolin-induced bI Cl (DbI Cl 5 45.7 6 9.4 mA/ cm 2 ; n 5 4) was inhibited by the presence of capsaicin (DbI Cl 5 33.0 6 10.1 mA/cm 2 ; n 5 4; P , 0.01).…”
Section: Effects Of Capsaicin On Basolateral CL 2 and K 1 Conductancementioning
confidence: 99%
“…Transepithelial potential (PD) was continuously measured by a high-impedance millivoltmeter that could function as a voltage clamp with automatic fluid resistance compensation (VCC-600, Physiologic Instruments, San Diego, CA) with a pair of calomel electrodes that were immersed in a saturated KCl solution and bridged to the modified Ussing chamber by a pair of polyethylene tubes filled with a solution of 2% (wt/vol) agarose in a 2 M KCl solution (18,19,22,38). I sc was measured by the amplifier (VCC-600) with a pair of silver-silver chloride electrodes that were immersed in a 2 M NaCl solution and bridged to the modified Ussing chamber by a pair of polyethylene tubes filled with a solution of 2% (wt/vol) agarose in a 2 M NaCl solution (1,(42)(43)(44). When the I sc was measured, the PD was clamped to 0 mV for 1 s by the amplifier.…”
Section: Measurement Of Iscmentioning
confidence: 99%
“…The water secretion across epithelial tissues is driven by epithelial Cl − secretion [13]. The epithelial Cl − secretion consists of two steps: (1) the Cl − -entry step across the basolateral membrane via Cl − transporter participating in Cl − uptake into the intracellular space such as Na + -K + -2Cl − cotransporter (NKCC) and (2) the Cl − -releasing step across the apical membrane via Cl − channels such as cystic fibrosis transmembrane conductance regulator (CFTR) Cl − channel at the apical membrane [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids and flavonoid-like compounds have various actions in cell function [8, 9]. Our previous studies have reported that a flavonoid, quercetin, elevates epithelial Cl − secretion under basal conditions, but decreases it under cAMP-stimulated conditions [10] by modifying activity of NKCC [3]. These reports suggest that quercetin regulates the activity of NKCC leading epithelial Cl − secretion to a moderate level irrespective of cAMP-induced stimulation and that quercetin would be a useful compound to achieve a moderate level of epithelial Cl − secretion.…”
Section: Introductionmentioning
confidence: 99%